Thermodynamic and transport properties of plasmas including silicon-based compounds. (3rd January 2018) - Colonna, G; D'Angola, A; Pietanza, L D; Capitelli, M; Pirani, F; Stevanato, E; Laricchiuta, A
Abstract: The characterization of the thermodynamic and transport properties of plasmas including silicon species could be of great interest for the investigation of many different systems containing the product of the ablation of silicon-based materials. Different plasma systems (pure silicon, silicon–argon, silicon dioxide and silicon carbide) have been investigated in a wide temperature range (10 3 –4 10 4 K) and for different pressures (1, 10, 30 and 100 atm), relying on the construction of accurate and extended databases of internal energy levels and binary-interaction transport cross sections for the silicon compounds. The results have been compared with the available results in the literature also studying the dependence on the ratio of components.